Prevalence of hospitalization for venous ulcers in adults in Brazil, Rio Grande do Sul and Santa Maria: historical series (Research, Society and Development, 2020)
Objective: to analyze the historical series in the period from 2008 to 2018 of the prevalence of hospitalization for venous ulcers in adults in Brazil, in the State of Rio Grande do Sul and in the municipality of Santa Maria. Method: documentary epidemiological study, historical series of the prevalence of hospital admissions for venous ulcers in the last 10 years. Results: when comparing the three locations, it is evident that in the state of Rio Grande do Sul there is a higher prevalence of hospital admissions, female and aged 50 to 59 years. Conclusion: Venous ulcers are lesions that require a varied demand for care and represent a long period of treatment, being able to be accompanied by professionals working in PHC, especially those in Nursing.